Study of drying kinetics and moisture diffusivity in iron ore briquettes after using different drying techniques - Sharma, Rishi; Nimaje, Devidas Sahebraoji (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
This study aimed to investigate the drying kinetics, effective moisture diffusivity and thermal degradation properties of iron ore briquettes using hot air drying, microwave drying, and infrared drying methods. The results showed that in both hot air and infrared drying, drying occurs gradually, starting with drying of the outer surface and gradually moving towards the inner core of the briquette. In microwave drying, the iron ore briquette is heated from the inside out. The moisture diffusion capacity is moderate at 100 W, lower at 180 W, and very high at 300 W. In both hot air and infrared drying, the moisture diffusivity is low at 105 °C, and the maximum strength is observed at 120 °C. The compressive strength was analyzed after applying the different drying methods, and the highest strength of 4.195 N/mm² was measured at 120 °C in the infrared chamber. The kinetic drying curves for the hot air, microwave, and infrared methods were analyzed using five different moisture ratio (MR) models: Newton, Henderson and Pabis, Logarithmic, Diffusion, and Wang & Singh. This research will provide valuable insight into the degradation of iron ore briquettes after the optimal removal of approximately 90% of the moisture from the sample. This approach will also guide the production of high quality dried products and assist in the production of green briquettes with lower carbon emissions. In this work, heat induration is used for drying as opposed to techniques such as sintering and nodulation where the agglomerates are heated at high temperatures of about 1100 °C and higher carbon emissions are produced.
Keywords: Moisture diffusivity; Iron ore briquette; Drying kinetics; Compressive strength